Cutaneous manifestations of COVID-19 in a tertiary COVID-19 referral hospital in the PhilippinesCapsule Summary - Cyrene C. Tan, MD; Belen L. Dofitas, MD, FPDS; Ma. Lorna F. Frez, MD, FPDS; Celina Daia D. Yap, MD; Jeanie Karen K. Uy, MD; Cynthia P. Ciriaco-Tan, MD, FPDS (Elsevier, 2022)
Background: Reports on COVID-19 skin manifestations and associated clinical outcomes are limited. Like viral diseases, cutaneous findings may be present and can help in confirmation and prognostication among those suspected or diagnosed with COVID-19. Objective: To determine COVID-19 cutaneous manifestations and their association with disease severity and course. Methods: This study was conducted in a designated COVID-19 referral hospital from January 1 to March 31, 2021. Skin manifestations recorded from January 1 to February 17 were retrospectively gathered. Reports from February 18 to March 31 were prospectively collected using a dermatologic checklist which was incorporated into all official medical records. Results: A total of 507 confirmed patients with COVID-19 were included. COVID-19 skin signs were detected in 39 patients (7.7%). Morbilliform lesions were most common. Skin signs were significantly associated with severe or critical cases (odds ratio, 3.4; 95% CI, 1.3-8.7) and mortality (relative risk, 2.9; 95% CI, 2.0-4.2). Limitations: Underestimation of prevalence of COVID-19 skin signs due to exclusion of outpatient and discharged patients and the subjective assessment in the retrospective part. Conclusion: Cutaneous signs were significantly associated with severe/critical COVID-19 as well as death among 507 hospitalized patients in a Philippine COVID-19 referral hospital.